Comparison of diagnostic and treatment processes among pediatric and adolescents and young adults’ populations suffering from acute lymphoblastic leukemia and lymphomas - Abdulaziz-Opiela, Gazala; Sobieraj, Anna; Płotka, Anna; Więckowska, Barbara; Gil, Lidia; Derwich, Katarzyna (Frontiers in Oncology, 2023)
Acute lymphoblastic leukemia (ALL) and lymphomas affect both pediatric and adult populations, therefore, they might be treated by pediatric or adult centers. It has been proven that the prognosis among adolescents and young adults (AYA) is poorer than among children, which remains a subject of research. Many factors are suspected to affect the diagnostic and treatment processes in adolescents and young adults, one of them being the organization of the healthcare system. The aim of the study was to compare the time intervals between different events on disease trajectory in pediatric and AYA groups suffering from ALL and lymphomas. We collected data on 81 patients diagnosed with ALL (50 children and 31 AYAs) and 100 patients diagnosed with lymphomas (50 children and 50 AYAs). Statistical analysis was performed in order to compare the groups. The results confirmed the hypothesis that the duration of the diagnostic process differs significantly between groups. For patients with ALL, the analyzed time intervals were significantly shorter in the pediatric group than in the AYA group: first contact with a GP - admission to Hematology Department (2 vs. 5 days; p-value=0.004), first contact with a GP - treatment (6 vs. 12 days, p-value=0.001), diagnosis - treatment (1 vs. 3 days, p-value=0.003). In the case of patients suffering from lymphomas, the results were similar. The analyzed time intervals were significantly shorter in the pediatric group than in the AYA group: first contact with a GP- diagnosis (21 vs. 40.5 days, p-value<0.0001), first contact with a GP - treatment (27 vs. 65 days, p-value<0.0001). Trend analysis showed that the longer patients had presented symptoms before contacting the primary care physician, the longer they waited for the beginning of treatment both in ALL and lymphomas groups (p-values=0.0129 and 0.0038 respectively). As the diagnostic and treatment processes are longer for AYA patients, actions must be undertaken in order to ensure equality and improve the healthcare system in Poland and possibly other countries.